Miniaturized Ceramic-Based Microbial Fuel Cell for Efficient Power Generation From Urine and Stack Development - Gajda, Iwona; Stinchcombe, Andrew; Merino-Jimenez, Irene; Pasternak, Grzegorz; Sanchez-Herranz, Daniel; Greenman, John; Ieropoulos, Ioannis A. (Frontiers in Energy Research, 2018)
One of the challenges in Microbial Fuel Cell (MFC) technology is the improvement of the power output and the lowering of the cost required to scale up the system to reach usable energy levels for real life applications. This can be achieved by stacking multiple MFC units in modules and using cost effective ceramic as a membrane/chassis for the reactor architecture. The main aim of this work is to increase the power output efficiency of the ceramic based MFCs by compacting the design and exploring the ceramic support as the building block for small scale modular multi-unit systems. The comparison of the power output showed that the small reactors outperform the large MFCs by improving the power density reaching up to 20.4 W/m3 (mean value) and 25.7 W/m3 (maximum). This can be related to the increased surface-area-to-volume ratio of the ceramic membrane and a decreased electrode distance. The power performance was also influenced by the type and thickness of the ceramic separator as well as the total surface area of the anode electrode. The study showed that the larger anode electrode area gives an increased power output. The miniaturized design implemented in 560-units MFC stack showed an output up to 245 mW of power and increased power density. Such strategy would allow to utilize the energy locked in urine more efficiently, making MFCs more applicable in industrial and municipal wastewater treatment facilities, and scale-up-ready for real world implementation.